PERENCANAAN STRUKTUR JEMBATAN LEMAH IRENG 1 JALAN TOL SEMARANG – SOLO - Dimas Prasetyo Nugroho; Sidqi Muhammad; Sri Tudjono; Sukamta Sukamta (Jurnal Karya Teknik Sipil, 2013)
Lemah Ireng 1 Bridge is located at Semarang – Solo Toll Road Phase I Section Ungaran – Bawen Package V Tinalun – Lemah Ireng. This bridge was constructed due to a deep ravine at Lemah Ireng Village, so necessary this bridge as a part of the toll road. This bridge is designed using prestressed concrete box girder construction. The method of execution is used by balance cantilever with cast in place box girder. The equipment which is used in the work of box girder is traveller. The length of the bridge is 879 m, which is divided into 8 spans. The bridge with length of 879 m requires complex planning in order to obtain efficient results. This bridge has two abutments and seven piers. Design of this bridge began of planning do the pre-dimension on top of the structure. The dimensions of box girder on this bridge are different in each segment with a shape like a parabola. The next step is analyzing loads incurred, including its own weight, additional dead load, traffic load, wind load, and earthquake load. From the results of this analysis is then performed structural analysis with the program SAP2000 to output results axial force, moment, shear, and torsion. The output of it is able to calculated loss of prestressing force, needs of tendon, and reinforcement of box girder. Sub structures are planned with do the pre-dimension of pier and calculating its strength by biaxial bending Bresler method. A Result from these calculations obtained pier reinforcement ratio is 1%. The next step is calculation of abutment with the first step do pre-dimension and calculated strengths and reinforcement needs. The final stage in the planning of this bridge is foundation of abutment and pier calculations. Calculation bore pile using Broms method for calculating moments received by the bore pile. Results from these calculations obtained bore pile reinforcement ratio is 1% for the abutments and pier amounted to 1.5%.